2021
DOI: 10.1111/jgh.15477
|View full text |Cite
|
Sign up to set email alerts
|

Gastric mucosal changes, and sex differences therein, after Helicobacter pylori eradication: A long‐term prospective follow‐up study

Abstract: Background and Aim: Improvement of atrophic gastritis and intestinal metaplasia (IM) is considered to reduce the gastric cancer risk, but whether it can be achieved by H. pylori eradication (HPE) remains controversial. To evaluate the effect of HPE, we observed the gastric mucosa for up to17 years after HPE and sex differences in gastric mucosa. Methods: In total, 172 patients (94 males, 78 females) with HPE were enrolled. Annual histological evaluations were performed for up to 17 years. The grades of mononuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…This consideration, and the fact and only a minority (approximately 5%) of patients with severe atrophic gastritis may progress to gastric cancer, justifies H. pylori eradication even at the advanced stage of severe chronic atrophic gastritis 365. At present endoscopic surveillance is required to follow up patients with severe atrophic gastritis following H. pylori eradication but in the near future the molecular characterisation of gastritis will provide a more reliable assessment of patients who are cured or protected from progression to gastric cancer 366 367…”
Section: Wg 4: Gastric Cancer and Preventionmentioning
confidence: 99%
“…This consideration, and the fact and only a minority (approximately 5%) of patients with severe atrophic gastritis may progress to gastric cancer, justifies H. pylori eradication even at the advanced stage of severe chronic atrophic gastritis 365. At present endoscopic surveillance is required to follow up patients with severe atrophic gastritis following H. pylori eradication but in the near future the molecular characterisation of gastritis will provide a more reliable assessment of patients who are cured or protected from progression to gastric cancer 366 367…”
Section: Wg 4: Gastric Cancer and Preventionmentioning
confidence: 99%
“…Vauhkonen et al reported that although DGC occurred frequently in the setting of atrophic gastritis and intestinal metaplasia, UGC often arose in the absence of these abnormalities [42]. Gastric atrophy and/or intestinal metaplasia are more severe in males than in females [43,44]; consequently, we suggest that the male preponderance of post-HPE DGC may be related to the differential sex-based severity of these predisposing conditions. Take also reported that UGC is more common in cases with mild gastric atrophy [14].…”
Section: Plos Onementioning
confidence: 69%
“…A diagnosis of endoscopic atrophy is based on the disap­pearance and discoloration of mucosal folds and increased vascular translucency. However, in many cases, it is difficult to evaluate the atrophic border, especially when the gastric mucosa is partially regenerated and the atrophy has improved after eradication treatment.‍ ( 29 ) Takeda et al ‍ ( 12 ) reported that LCI produced superior visibility of the atrophy boundary to that visualized by WLI alone in 42.1% of cases. Mizukami et al ‍ ( 18 ) also objectively evaluated the color difference of the atrophy boundary in the CIE 1976 L*a*b* color space, and reported that it was 14.79 ± 6.68 for LCI and 11.06 ± 5.44 for WLI; this difference was significant.…”
Section: Discussionmentioning
confidence: 99%
“…The color difference was also significantly different between people with a current infection and those who had been previously infected. Atrophy findings differ between endoscopic and histological methods and the degree of improvement in atrophy after eradication also differs when assessed using endoscopic and histological approaches.‍ ( 29 ) Especially after eradication, atrophy is improved, and atrophied and non-atrophied mucosa coexist, which often makes endoscopic diagnosis difficult. This divergence may disappear when endoscopy is combined with LCI.…”
Section: Discussionmentioning
confidence: 99%